2015
DOI: 10.1155/2015/126984
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Cytokines as Predictors of Macular Edema in Patients with Diabetes following Uncomplicated Phacoemulsification Cataract Surgery

Abstract: This study aims to ascertain whether cytokines in the aqueous humor can predict macular edema (ME) in diabetic patients following uncomplicated phacoemulsification cataract surgery. Undiluted aqueous humor samples were obtained from 136 consecutive type 2 diabetic patients who underwent cataract surgery. The concentrations of 27 cytokines were measured in aqueous humor using the multiplex bead immunoassay. At the final follow-up examination, 116 patients completed 4 weeks of follow-up, and the incidence of mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 38 publications
1
40
0
6
Order By: Relevance
“…However, these agents do not significantly reduce the macular thickness in eyes with DME after CS [8,9]. This is probably because cytokines other than VEGF are involved in the onset and the progression of DME after CS [5], and anti-VEGF agents cannot reduce the levels of these other cytokines in eyes with DME [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these agents do not significantly reduce the macular thickness in eyes with DME after CS [8,9]. This is probably because cytokines other than VEGF are involved in the onset and the progression of DME after CS [5], and anti-VEGF agents cannot reduce the levels of these other cytokines in eyes with DME [10].…”
Section: Introductionmentioning
confidence: 99%
“…Cataract surgery (CS) has a high risk of causing and advancing DME because there is a causal relationship between the perioperative inflammation and the bloodretinal barrier breakdown in patients with diabetic retinopathy [3,4]. A recent study found that several cytokines -including interleukin-6 (IL-6), IL-8, IL-10, IL-1β, interferon-induced protein-10 (IP-10), monocyte chemotactic protein-1 (MCP-1), and vascular endothelial growth factor (VEGF) -were significantly higher in patients with DME after CS [5]. These inflammatory cytokines are associated with the breakdown of the bloodretinal barrier, which leads to increased vascular permeability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Данные ли-тературы, свидетельствуют о том, что увеличение содержания ИЛ 8 ассоциируется с высокой степе-нью глиотической облитерации сосудов [8], а так-же является маркером воспалительно-деструктивных изменений в местах повреждений [9]. Увеличение содержания ИЛ-8 при ПЭС в соче-тании с глаукомой может свидетельствовать о раз-носторонних механизмах нарушений, и соответст-вует исследованиям [19].…”
Section: Ninaluts2@gmailcomunclassified
“…Increased intraocular cytokines have been observed in the vitreous fluid of patients with proliferative DR [54][55][56]. Interleukins (IL) such as IL-1 and IL-6 have been shown to play a role in the pathogenesis of DR by contributing towards the breakdown of blood-retinal-barrier.…”
Section: Interleukin Inhibitorsmentioning
confidence: 99%